Strategi dalam Meminimalisir Kesulitan Pembelajaran Kanji - Indah Fitriani; Pika Yestia Ginanjar (Universitas Diponegoro, 2022)
For Japanese language learners who come from non-Kanji countries, kanji is one of the most difficult parts of learning Japanese. Regarding the difficulties in learning kanji, in this discussion will be studied about the difficulties in learning kanji and strategies that can minimize the difficulties in learning kanji. To examine this subject, the method used is a qualitative descriptive method. From the results of the discussion, it can be concluded that to minimize difficulties in learning kanji, the strategy that can be done is to make references that can help students understand each part of kanji, and encourage students to practice writing kanji repeatedly. <a href=